Exploring the Dynamics of Spoken and Written Discourse: A Comparative Analysis ("Conference on Universal Science Research 2023", 2023)
This thesis aims to investigate the distinctive features, functions, and implications of spoken and written discourse, shedding light on their inherent differences, while also highlighting the interconnectedness and mutual influences between these two modes of communication.